Design of size uniform and controllable covalent organic framework nanoparticles for high-performance anticancer drug delivery. (March 2023) - Han, Guangze; Xiang, Shuo; Jiang, Kang; Zhang, Wei; Weng, Qunhong
Covalent organic frameworks (COFs) receive much attention in biomedicine because of their unique adsorption, optical and biological properties, as well as highly variable structures. However, preparation of nanosized COFs with uniform and controllable size is still a challenge. Herein, we develop a facile interfacial method to prepare the COF nanoparticles (COFNPs) with the uniform size of 30–50 nm from p-benzoquinone (BQ) and 4-[1, 2, 2-tris(4-aminophenyl)ethenyl]aniline (TPEA) by Michael addition. The TPEA-BQ COFNPs show positive zeta potential and effectively load the hydrophobic anticancer drug camptothecin (CPT) with the capacity of up to 127wt%, and remarkably improved the CPT dispersibility in water due to the retention of quinone structure. In vitro assay reveals CPT@ TPEA-BQ significantly reduced cell viability to 29% after 24 h incubation, much lower than that of free CPT (51%) at the same concentration of 10 μg mL −1 . Further in vivo experiment confirms the high anticancer drug delivery performance of the designed TPEA-BQ COFNPs. After 20 days of injection treatment, the CPT loaded in TPEA-BQ COFNPs inhibits the tumor growth by 60%, much higher than that of free CPT group (23%). This work demonstrates the feasibility to design advanced drug delivery systems based on highly structure-tunable COF system.